Analysis of the Determinants of Economic Growth in Border Areas of West Kalimantan Using Panel Data - Deffrinica; Shasta Pratomo, Devanto; Budi Santoso, Dwi; Hayet; Machimu, Joachimu; Kikky Vuspitasari, Benedhikta; Rini Hapsari, Veneranda (Universitas Gorontalo, 2026)
Economic growth in border regions plays a vital role in reducing regional disparities and strengthening national economic integration. Nevertheless, border areas in West Kalimantan continue to face structural challenges, particularly with regard to human capital quality, the effectiveness of fiscal transfers, and the utilization of infrastructure. This study aims to examine the determinants of economic growth in these regions using a panel data approach. The analysis incorporates average years of schooling, trade, Special Allocation Funds (DAK), General Allocation Funds (DAU), road infrastructure, and electricity as explanatory variables. The empirical model applies a Random Effects Model (REM) estimated through Generalized Least Squares (GLS). The findings reveal that average years of schooling has a positive and statistically significant effect on economic growth, highlighting the critical role of human capital in promoting regional development. In contrast, trade and General Allocation Funds (DAU) do not show statistically significant effects. Special Allocation Funds (DAK), as well as road and electricity infrastructure, exhibit significant negative effects, indicating that fiscal transfers and infrastructure provision have not yet been effectively translated into productive economic activity. These results suggest that, in the short term, economic growth in border regions is influenced more by improvements in human capital than by fiscal transfers and physical infrastructure. Therefore, policy efforts should prioritize strengthening human capital while enhancing the effectiveness of fiscal allocation and infrastructure utilization to support sustainable regional development.